Innovative study methods for the Mediterranean coralligenous habitats (2016)
Coralligenous habitats are of special interest in the Mediterranean Sea because they represent one of the most important biodiversity ‘hot-spots’ and are considered of great relevance for fisheries activities in the region. Despite their importance, however, there are missing consensual methodologies for their monitoring and, despite some attempts, no environmental or ecological quality indices have been established yet. This situation could be related to the difficulties associated with their exploration and their spatial heterogeneity. These habitats are in urgent need of efficient standard monitoring and management protocols programmes to develop an effective network for their conservation. Here we reviewed the available methodologies and robotics tools used to evaluate and monitor benthic habitats, highlighting the importance of defining rapid cost-effective sampling and analyses approaches and architectures for future monitoring of changes in coralligenous habitats based on current technological developments. We identified still images acquisitions as the most effective data gathering system. Stereo photogrammetry, photomosaic elaboration and three-dimensional (3D) modelling may largely improve the data analysis and therefore the quality status assessment of the coralligenous habitats. The advantage and efficiency of different approaches and methods, and whether they should be applied and standardised for further monitoring activities, were discussed.